Which Type of Antismoking Advertisement Is Perceived as More Effective? An Experimental Study With a Sample of Australian Socially Disadvantaged Welfare Recipients. Issue 3 (May 2017) - Guillaumier, Ashleigh; Bonevski, Billie; Paul, Chris; d'Este, Catherine; Durkin, Sarah; Doran, Christopher
Purpose: Evaluate the perceived effectiveness of key antismoking messages among highly disadvantaged smokers and assess the impact of nicotine dependence and cessation cognitions on message processing. Design: The experimental crossover trial, undertaken between March and December 2012, randomly exposed participants to two of three antismoking advertisements delivered via touchscreen computer. Setting: Welfare recipients were recruited from a community service organization in New South Wales, Australia. Subjects: Subjects were 354 smokers (79% response rate). Participants resided in government rental housing (52%), earned less than AUD400/wk (72%), and received their primary income from government welfare (95%). Intervention: Three 30-second antismoking television advertisements representing common campaign themes: why to quit (graphic imagery), why to quit (personal testimonial), or how to quit. Measures: An 11-item scale assessed perceived effectiveness and message acceptance. An eight-item cessation cognitions index assessed motivations and readiness to quit, and the heaviness of smoking index was used to classify nicotine dependence. Analysis: Descriptive statistics, generalized linear mixed models, and multiple linear regression analyses are reported. Results: Why-to-quit advertisements were perceived as significantly more effective than the how-to-quit advertisement (all p < .0001). Smokers with positive cessation cognitions were more likely to accept antismoking messages (p = .0003) and perceive them as effective (p < .0001). Nicotine dependence level did not influence message acceptance (p = .7322) or effectiveness (p = .8872). Conclusion: Highly emotive advertisements providing good reasons to quit may be the most effective in promoting the antismoking message among groups with high smoking rates.